Assessment of Xylem Discs from Fruiting and Shading Plants in Tap Water Desalination - Lubbad, Said H.; Elfarram, Atta (Current Green Chemistry, 2022)
Aims and Background: The low rainwater recharge rate and high seawater intrusion into the water aquifer present a dilemma of high ground-water salinity for the narrow coastal Gaza Strip. Thus, extremely saline water causes impairment to household appliances and deteriorates the performance of the reverse-osmosis desalination units. Methods: Accordingly, xylem discs of different plants, such as Mulberry, Pomegranate, Olives, Centroza, and Ficus, were investigated for desalination of tap water by flow-through experimentation. Various parameters such as the total dissolved salt of the inflow water, disc thickness, flow rate and the type of plant were investigated. Finally, the morphology of the xylem discs of the five plants was screened using an optical microscope. Results and Discussion: It was found that the xylem of different plants showed dissimilar efficiencies in water desalination. Thus, Centroza established the highest desalination efficiency of 31%, followed by Olive and Ficus as 26 and 25%, respectively, while Pomegranate and Mulberry established the poorest salt removal at 17 and 14%, respectively. Successive three-disc set up established 50% desalination of inflow-water of 5000 ppm. Conclusion: Hence, a disposable cost-effective xylem desalination unit is proposed as a guard filter to be installed between the faucet and household desalination units and washing machines or dishwashers, in order to improve the performance and extend the life-time of these appliances.
Keywords: xylem desalination unit